CONTEMPORARY PROBLEMS OF PHYSICAL CULTURE AND MASS SPORTS - Sharofiddin Maxmudov (Proximus Journal Publishing, 2025)
The article examines the development of physical culture and sports in Uzbekistan in the years of independence. It analyzes state policy measures aimed at popularizing sports, promoting a healthy lifestyle, physical rehabilitation of people with disabilities, and training talented athletes. Particular attention is paid to regulations and decrees regulating the sphere of physical culture and sports, as well as the importance of a scientific approach in the development of this area. The problems of personnel training, reduction of scientific potential are considered and measures for their solution are proposed
Keywords: physical culture; physical cultureimprovement; development